2015
DOI: 10.1016/j.watres.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioassays to evaluate complex chemical mixtures in recycled water

Abstract: With burgeoning population and diminishing availability of freshwater resources, the world continues to expand the use of alternative water resources for drinking, and the quality of these sources has been a great concern for the public as well as public health professionals. In vitro bioassays are increasingly being used to enable rapid, relatively inexpensive toxicity screening that can be used in conjunction with analytical chemistry data to evaluate water quality and the effectiveness of water treatment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 73 publications
8
86
1
Order By: Relevance
“…Advanced oxidation processes (AOPs) like ozone and UV with addition of hydrogen peroxide and other oxidants has proven to remove many TOrCs present in municipal wastewater (Wert et al, 2009;Wols et al, 2013;Park et al, 2015). However, studies also have shown that these AOPs result in transformation products, some of which are more toxic than the precursor compounds (Rizzo, 2011;Jia et al, 2015). Adsorption processes like granular activated carbon (GAC) and powdered activated carbon (PAC) are capable of removing significant amounts of TOrCs from water without forming byproducts Redding et al, 2009;Altmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) like ozone and UV with addition of hydrogen peroxide and other oxidants has proven to remove many TOrCs present in municipal wastewater (Wert et al, 2009;Wols et al, 2013;Park et al, 2015). However, studies also have shown that these AOPs result in transformation products, some of which are more toxic than the precursor compounds (Rizzo, 2011;Jia et al, 2015). Adsorption processes like granular activated carbon (GAC) and powdered activated carbon (PAC) are capable of removing significant amounts of TOrCs from water without forming byproducts Redding et al, 2009;Altmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions of the study demonstrated that while there are limitations to bioassay techniques, they are a valid tool for water quality assessment that complement chemical analyses. A recent study incorporating 36 bioassays covering 18 biological endpoints indicated that a suite of bioassays can be useful in characterizing multiple toxicological pathways relevant to human health and can guide decision-making with regard to the treatment processes (Jia et al 2015). The science advisory panel, which convened in 2018 to evaluate risks from CECs in water treated for reuse, recommended that estrogen receptor alpha and the aryl hydrocarbon receptor bioassays be used to respectively assess estrogenic and dioxin-like biological activities in recycled water (Drewes et al 2018).…”
Section: Spectroscopymentioning
confidence: 99%
“…Especially, there are many chemicals are not readily identied because of their unknown structure, lack of pure sample preparation and detection method. 4,43,44 The rapid, less expensive and highthroughput technology was pursued, that could screen thousands of chemicals for potential genotoxicity in a relatively simple way. The rst use of a toxicity equivalence-like method for risk assessment purposes was described by Eadon et al (1986).…”
Section: Mixture Effects Of the Known Componentsmentioning
confidence: 99%
“…2,3 Moreover, these chemical monitoring methods are generally targeted to specic individual or groups of compounds, and do not provide information about health impacts or cumulative effects from complex mixture interactions. 4 These push forward the development of sensitive, cost-effective and relatively simple bacterial bioassays which can indicate the presence of unknown genotoxic chemicals, also estimate the contribution of unknown chemicals and chemicals below detection limits to the overall mixture effect.…”
Section: Introductionmentioning
confidence: 99%